IgG4-related Orbital Disease and Its Mimics in a Western Population. (December 2015) - Ferry, Judith A.; Klepeis, Veronica; Sohani, Aliyah R.; Harris, Nancy Lee; Preffer, Frederic I.; Stone, John H.; Grove, Arthur; Deshpande, Vikram
Abstract : Although chronic inflammatory disorders of the ocular adnexa are relatively common, their pathogenesis is in many cases poorly understood. Recent investigation suggests that many cases of sclerosing orbital inflammation are a manifestation of IgG4-related disease; however, most patients reported have been Asian, and it is not clear whether the results of studies from the Far East can be reliably extrapolated to draw conclusions about Western patients. We evaluated 38 cases previously diagnosed as orbital inflammatory pseudotumor or chronic dacryoadenitis to determine whether our cases fulfill the criteria for IgG4-RD (IgG4-related dacryoadenitis when involving the lacrimal gland, and IgG4-related sclerosing orbital inflammation when involving orbital soft tissue). Fifteen patients had IgG4-related dacryoadenitis or orbital inflammation. These patients included 9 men and 6 women, aged 24 to 77 years (median, 64 y). Lesions involved orbital soft tissue (8 cases), lacrimal gland (6 cases), and canthus (1 case). In 1 case, focal in situ follicular neoplasia was seen in a background of IgG4-RD. In another case, a clonal IGH gene rearrangement was detected. Four patients with IgG4-RD had evidence of IgG4-RD in other anatomic sites. Five patients, 1 man and 4 women, aged 26 to 74 years (median 50 y) had orbital lesions (2 involving lacrimal gland, 3 involving soft tissue) suspicious for, but not diagnostic of, IgG4-RD. Of 16 patients with IgG4-RD or probable IgG4-RD with information available regarding the course of their disease, 11 patients experienced recurrent or persistent orbital disease. However, no patient developed lymphoma, and no patient died of complications of IgG4-RD. Eighteen patients had lesions not representing IgG4-RD. They included 6 male and 12 female individuals aged 6 to 77 years (median, 47 y). These patients had a variety of diseases, including granulomatosis with polyangiitis (3 cases), Rosai-Dorfman disease (1 case), nonspecific chronic inflammation and fibrosis involving lacrimal gland or soft tissue (12 cases), and others. Clinical and pathologic findings among our patients with IgG4-RD involving the orbit are similar to those previously described in Asian patients. Careful evaluation of histologic and immunophenotypic features and clinical correlation are required to distinguish orbital IgG4-RD from other sclerosing inflammatory lesions in the orbit. Abstract : Supplemental Digital Content is available in the text.